2011
DOI: 10.3109/10826084.2011.552932
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Popularity of Prescription Opioid Injection in Downtown Montréal: New Challenges for Harm Reduction

Abstract: Starting in 2007, a 2-year study based on ethnographic methodology was carried out downtown Montréal, Canada. A thematic analysis of observational and interview-based notes was conducted. Illicit prescription opioid (PO) use was widespread among street-based participants. Injection was the main mode of PO administration observed among users. Some injection practices such as “doing a wash” could pose new challenges in terms of prevention of infections. More research is needed to examine the role of illicit PO u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 40 publications
7
90
0
2
Order By: Relevance
“…For drug residue injection, it can be hypothesized that, compared to legal income sources, marginal or criminal sources of income likely produce more irregular or weak income streams, which could force PO injectors to fall back on PO residues. These results are consistent with prior ethnographic studies reporting that residue injection is mainly practiced by PWID with low-income sources or unsuccessful income-generating strategies (Bourgois, 1998;Bourgois and Schonberg, 2009;Roy et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For drug residue injection, it can be hypothesized that, compared to legal income sources, marginal or criminal sources of income likely produce more irregular or weak income streams, which could force PO injectors to fall back on PO residues. These results are consistent with prior ethnographic studies reporting that residue injection is mainly practiced by PWID with low-income sources or unsuccessful income-generating strategies (Bourgois, 1998;Bourgois and Schonberg, 2009;Roy et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Reports of PO injection have risen worldwide, including in the United States (Davis and Johnson, 2008;Young et al, 2010;Surrat et al, 2011;Lankenau et al, 2012;Black et al, 2013;MateuGelabert et al, 2015), Europe (Partanen et al, 2009;Keijzer and Imbert., 2011;Roux et al, 2011), South Asia (Larance et al, 2011) and Australia (Degenhardt et al, 2006). In Canada, over the past decade, PO injection has gained in popularity among drug users across the country (UHRI, 2013; Leclerc et al, 2013;Firestone and Fischer, 2008;Roy et al, 2011;Roy et al, 2013;Bruneau et al, 2012;Fischer et al, 2006;PHAC, 2014). Data from I-Track, a multisite surveillance system that monitors HIV and hepatitis C virus (HCV) infection rates and associated risk behaviors among persons who inject drugs (PWID) in Canada, revealed that hydromorphone, morphine and oxycodone, either in tablet or capsule form, were injected more often than heroin.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations